PENGEMBANGAN MEDIA PAPAN KARTU AKSARA JAWA [PAKARJA] GUNA MENINGKATKAN MINAT BACA AKSARA JAWA LEGENA PADA SISWA - Sari, Erma Novita; ‘Aziizah, Nadine; Asri, Oktara Rossiana; Vistiana, Jenniver; Setiawaty, Rani; Najikhah, Fatikhatun (Universitas Muria Kudus, 2024)
This study aims to: 1] Develop learning media in the form of Javanese script board media on Javanese legena script material 2] Knowing student responses to the feasibility of learning media in the form of Javanese on Javanese legena script material in the form of Javanese script board media for grade 3 students SD. RD research adopting development from Borg Gall. The results of this study are: 1) Learning media has been developed in the form of PAKARJA BOARDS (Javanese script card boards) in the form of board and card media. 2) The feasibility of the PAPAN PAKARJA learning media that has been developed is very feasible with a percentage of 90% based on the final stage material expert assessment after improvement of the design expert with a percentage of 82.5% with feasible criteria. 3) With a percentage of 81.2% teacher assessment with proper criteria. 4) The results of student responses with a percentage of 90% with feasible criteria. 5) The average pretest score is 78 and the posttest score is 98, so the biggest percentage increase is 26%. Based on these results, it can be concluded that the PAPAN PAKARJA learning media is suitable for increasing reading interest in learning Javanese script in the Legenda Javanese script material.